An Actin Homolog of the Archaeon Thermoplasma acidophilum That Retains the Ancient Characteristics of Eukaryotic Actin - Hara, Futoshi (American Society for Microbiology, 2007)
Actin, a central component of the eukaryotic cytoskeleton, plays a crucial role in determining cell shape in addition to several other functions. Recently, the structure of the archaeal actin homolog Ta0583, isolated from the archaeon Thermoplasma acidophilum, which lacks a cell wall, was reported by Roeben et al. (J. Mol. Biol. 358:145-156, 2006). Here we show that Ta0583 assembles into bundles of filaments similar to those formed by eukaryotic actin. Specifically, Ta0583 forms a helix with a filament width of 5.5 nm and an axial repeating unit of 5.5 nm, both of which are comparable to those of eukaryotic actin. Eukaryotic actin shows a greater resemblance to Ta0583 than to bacterial MreB and ParM in terms of polymerization characteristics, such as the requirement for Mg(2+), critical concentration, and repeating unit size. Furthermore, phylogenetic analysis also showed a closer relationship between Ta0583 and eukaryotic actin than between MreB or ParM and actin. However, the low specificity of Ta0583 for nucleotide triphosphates indicates that Ta0583 is more primitive than eukaryotic actin. Taken together, our results suggest that Ta0583 retains the ancient characteristics of eukaryotic actin.